2005
DOI: 10.2337/diabetes.54.1.251
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Long-Acting Insulin Analog Using Albumin Fusion Technology

Abstract: The primary therapeutic goal for the treatment of diabetes is maintenance of a long-term, near-normoglycemic condition and prevention of the onset or progression of the complications associated with the disease. Although several analogs of human insulin have been developed, the currently prescribed long-acting insulin analogs do not provide a stable basal glycemia for more than a few hours. Here, we report the development of Albulin, a long-acting insulin analog obtained by direct gene fusion of a singlechain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
60
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 35 publications
5
60
0
Order By: Relevance
“…Thus, RSA had a t1 ⁄2 ␣ ϭ 4.1 h and a t1 ⁄2 ␤ ϭ 49.1 h, whereas HSA had a t1 ⁄2 ␣ ϭ 0.8 h (48 min) and a t1 ⁄2 ␤ ϭ 14.8 h. Our HSA fusion proteins showed similar or even better values in mice with t1 ⁄2 ␣ between 37 and 117 min and a t1 ⁄2 ␤ between 40 and 47 h indicating that the antibody fusion part (probably through increase in size of the fusion protein) also contributes to prolonged circulation time. This finding is in accordance with results of various other HSA fusion proteins, which showed improved pharmacokinetic properties in various animals including mice (25,(27)(28)(29). In addition, improved therapeutic activities were observed for HSA fusion proteins (25)(26)(27)(28).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, RSA had a t1 ⁄2 ␣ ϭ 4.1 h and a t1 ⁄2 ␤ ϭ 49.1 h, whereas HSA had a t1 ⁄2 ␣ ϭ 0.8 h (48 min) and a t1 ⁄2 ␤ ϭ 14.8 h. Our HSA fusion proteins showed similar or even better values in mice with t1 ⁄2 ␣ between 37 and 117 min and a t1 ⁄2 ␤ between 40 and 47 h indicating that the antibody fusion part (probably through increase in size of the fusion protein) also contributes to prolonged circulation time. This finding is in accordance with results of various other HSA fusion proteins, which showed improved pharmacokinetic properties in various animals including mice (25,(27)(28)(29). In addition, improved therapeutic activities were observed for HSA fusion proteins (25)(26)(27)(28).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, HSA has also been successfully used to generate fusion proteins, e.g. with hormones (insulin, human growth hormone) (25,26) and cytokines (interferon-␣, interferon-␤, IL-2) (27)(28)(29), to reduce immunogenicity and modulate the pharmacokinetic properties, thus improving therapeutic efficacy of these molecules. Improved pharmacokinetic properties have also been described for a scFv-HSA fusion protein as well as for F(abЈ) and F(abЈ) 2 conjugated to rat serum albumin (RSA) for the targeting of human tumor necrosis factor (20).…”
mentioning
confidence: 99%
“…To obtain a form of CocH that might be developed as a protein therapeutic, we fused this recombinant BChE at its C terminus with human serum albumin. Similar fusion proteins have been observed to possess favorable pharmacokinetic properties with high stability and extended plasma half lives (Duttaroy et al, 2005). In work that is being reported elsewhere (Gao and Brimijoin, unpublished results), we observed that the mutant BChE-albumin fusion, 'Albu-CocH' retains high catalytic efficiency with cocaine (k cat ¼ 2700 min À1 , K m ¼ 2 mM) and exhibits a plasma half-life of 8 h after i.v.…”
Section: Introductionsupporting
confidence: 80%
“…Interestingly, despite the postulated close interaction of the two insulin binding sites within the InsR, a fusion protein between insulin and albumin (albulin) is also equipotent to wild-type insulin both in vitro and in vivo (41).…”
Section: Discussionmentioning
confidence: 99%